Employability among people with uncontrolled seizures: An interpretative phenomenological approach - Wo, M.C.M.; Lim, K.S.; Choo, W.Y.; Tan, C.T. (Elsevier, 2015)
Purpose: This study aimed to explore positive and negative factors affecting the employability in patients with uncontrolled seizures. Method: Semistructured interviews with 21 patients with uncontrolled seizures were analyzed using interpretative phenomenological analysis. Result: Eleven (52.4%) of the participants interviewed were employed; 7 were holding full-time position with more than 4. years of working experience. The mean age was 34.6. years, 71.4% were female, 38% were married, 71.4% had at least 11. years of education, 38% had a driving license, 19% received government monetary aid, 66.7% had seizure onset before reaching 17. years of age, 66.7% experienced monthly seizures, and 76% were on polytherapy. A total of 6 main themes were found to be affecting the employability among people with uncontrolled seizures: (a) ability to work; (b) intention to work; (c) support and stigma at workplace; (d) family support, overdependence, and protection; (e) life event; and (f) government and welfare support. Subthemes under the main theme ability to work included education, cognitive and physical functions, ability to continue working after seizures, ability to travel to work, self-perceived ability to work, and ability to cope with stress. Many shared the same idea that employment is important, but their intention to work varied. The employed group tended to work for a future goal and self-satisfaction, and the unemployed group tended to have no or lack intention to work. Positive factors were noted in the following themes: ability to work; intention to work; support and stigma at workplace; and family support, overdependence, and protection. Conclusion: There were internal and external factors affecting the employability among people with uncontrolled seizures both positively and negatively. Positive internal factors such as ability and intention to work require further exploration.